Speciation of cesium in a radiocesium-bearing microparticle emitted from Unit 1 during the Fukushima nuclear accident by XANES spectroscopy using transition edge sensor - Yoshio Takahashi; Hikaru Miura; Shinya Yamada; Oki Sekizawa; Kiyofumi Nitta; Tadashi Hashimoto; Takumi Yomogida; Akiko Yamaguchi; Shinji Okada; Takaaki Itai; Hiroki Suga; Teruhiko Kashiwabara; et al. (Journal of Hazardous Materials, 2025)

Different acute toxicity of fipronil baits on invasive Linepithema humile supercolonies and some non-target ground arthropods - Daisuke Hayasaka; Naoki Kuwayama; Azuma Takeo; Takanobu Ishida; Hiroyuki Mano; Maki N. Inoue; Takashi Nagai; Francisco Sánchez-Bayo; Koichi Goka; Takuo Sawahata (Ecotoxicology, 2015)

Breeding system, colony and population structure in the weaver ant Oecophylla smaragdina - E.A. SCHLÜNS; B.J. WEGENER; H. SCHLÜNS; N. AZUMA; S. K. A. ROBSON; R. H. CROZIER (Molecular Ecology, 2009)
Weaver ants ( Oecophylla smaragdina ) are dominant ants in open forests from India, Australia, China and Southeast Asia, whose leaf nests are held together with larval silk. The species, together with its sole congener O. longinoda , has been important in research on biological control, communication, territoriality and colony integration. Over most of the range, only one queen has been found per colony, but the occurrence of several queens per nest has been reported for the Australian Northern Territory. The number of males mating with each queen is little known. Here we report on the colony structure of O. smaragdina using published and new microsatellite markers. Worker genotype arrays reflect the occurrence of habitual polygyny (more than one queen per colony) in 18 colonies from Darwin, Northern Australia, with up to five queens inferred per colony. Monogyny (one queen per colony) with occasional polygyny was inferred for 14 colonies from Queensland, Australia, and 20 colonies from Java, Indonesia. Direct genotyping of the sperm carried by 77 Queensland queens and worker genotypic arrays of established colonies yielded similar results, indicating that less than half of the queens mate only once and some mate up to five times. Worker genotype arrays indicated that queens from Java and the Northern Territory also often mate with more than one male, but less often than those from Queensland. A strong isolation‐by‐distance effect was found for Queensland samples. The variation uncovered means that O. smaragdina is a more versatile study system than previously supposed.

Synchronized development of gonad and bioluminescent light organ in a highly sexually dimorphic leiognathid fish, Photoplagios rivulatus - K. Ikejima; M. Wada; K. Kita-Tsukamoto; T. Yamamoto; N. Azuma (Marine Biology, 2008)

Genetic structure of masu salmon ( Oncorhynchus masou ) populations in Hokkaido, northernmost Japan, inferred from mitochondrial DNA variation - S. Kitanishi; K. Edo; T. Yamamoto; N. Azuma; O. Hasegawa; S. Higashi (Journal of Fish Biology, 2007)
Genetic structure of masu salmon Oncorhynchus masou populations in Hokkaido was examined by analysing mtDNA NADH dehydrogenase subunit 5 gene (561 bp) of 382 individuals collected from 12 rivers, in which there were no records of artificial release. Analysis of molecular variance showed that between groups level and between populations within‐group level explained each c. 10% of genetic variance. In neighbour‐joining tree, four populations located in southern Hokkaido were clustered into a single group; however, other populations did not form any clear clusters. Fu’s F S , Tajima’s D and a mismatch distribution test indicated a sudden expansion of population in the entire population of Hokkaido and the northernmost population of Chiraibetsu, which was genetically close to the southern Hokkaido group. The Sea of Japan and southern rivers, including those of southern Hokkaido, seem to have served as refugia for masu salmon during glacial periods, and their dispersal and straying in interglacial periods affected the genetic structure of masu salmon populations in Hokkaido.

Salmon gonadotropes secrete free form alpha (α)-subunit: quantitative analysis by the sandwich cell immunoblot assay - N. Naito; Y. Koide; T. Yada; T. Azuma; H. Kawauchi (Fish Physiology and Biochemistry, 2003)

Transfer of symbiotic luminous bacteria from parental Leiognathus nuchalis to their offspring - M. Wada; N. Azuma; N. Mizuno; H. Kurokura (Marine Biology, 1999)

Pharmacokinetics of an antifibrotic agent, pirfenidone, in haemodialysis patients - M. Taniyama; S. Ohbayashi; M. Narita; R. Nakazawa; S. Hasegawa; N. Azuma; S. Teraoka; K. Ota; S. Yamauchi; S. B. Margolin (European Journal of Clinical Pharmacology, 1997)